Penerapan Sistem Kependudukan Berbasis Web Sebagai Upaya Peningkatan Pelayanan di Desa Karangbendo - Farizqi Panduardi; Dianni Yusuf; Ruth Ema Febrita; Endi Sailul Haq; Agung Bahtiar; Azizatur Rohma (Indonesian Journal Publisher, 2025)
In 2011, Karangbendo Village in Rogojampi Subdistrict, Banyuwangi Regency, had a population of 6,891 residents spread across five hamlets. However, the village government still lacks a comprehensive and real-time digital database, which has hindered decision-making, particularly in distributing social aid. Data collection is still conducted manually using paper forms and the Dasawisma application, which is considered inefficient, making it difficult for officials to access up-to-date and accurate information. To address this, a web-based population system is being developed to enable digital storage and access, with training for village officials and volunteers to begin data input in July 2024. The project will be implemented in stages, starting with the data input feature, followed by training to reduce errors. After data input, additional training will focus on maximizing the system's features, and progress will be measured by the amount of data successfully entered. The web-based system has now been completed, and training for Dasawisma volunteers and village officials has taken place. System evaluation shows an user acceptance rate 4.13 of 5, with a goal of completing 60% of the population data by December 2024.